Development of intestinal ischemia/reperfusion-induced acute kidney injury in rats with or without chronic kidney disease: Cytokine/chemokine response and effect of α-melanocyte-stimulating hormone - Martin Skott; Rikke Nørregaard; Hanne Birke-Sørensen; Johan Palmfeldt; Tae-Hwan Kwon; Thomas Jonassen; Jørgen Frøkiær; Søren Nielsen (The Korean Society of Nephrology, 2014)
Background: The primary aim of the study was to investigate the cytokine/chemokine response in the kidney, lung, and liver following acute kidney injury (AKI). The secondary aim was to test whether α-melanocyte-stimulating hormone (α-MSH) could prevent a reduction in organ function, and attenuate the inflammatory cytokine/chemokine response within the kidney, lung, and liver following AKI in rats with or without preexisting chronic kidney disease (CKD). Methods: A two-stage animal model, in which AKI was induced in rats with preexisting CKD, induced by 5/6 nephrectomy (Nx), was used. Six weeks later, AKI was induced by intestinal ischemia and reperfusion (IIR). Sham procedures [S(Nx) and S(IIR)] were also performed. Results: Increasing levels of serum creatinine (sCr) demonstrated progressive development of CKD in response to Nx, and following IIR sCr levels increased further significantly, except in the S(Nx) group treated with α-MSH. However, no significant differences in the fractional increase in sCr were observed between any of the groups exposed to IIR. In kidney, lung, and liver tissue the levels of interleukin (IL)-1β were significantly higher in rats undergoing IIR when compared to the S(IIR) and control rats. The same pattern was observed for the chemokine monocyte chemoattractant protein (MCP)-1 in lung and liver tissue. Furthermore, kidney IL-1β and RANTES levels were significantly increased after IIR in the Nx rats compared to the S(Nx) rats. Conclusion: Both the functional parameters and the cytokine/chemokine response are as dramatic when AKI is superimposed onto CKD as onto non-CKD. No convincing protective effect of α-MSH was detected.